Plato and the Mystery of False Belief in Theaetetus - Ahmad Asgari; maedeh eslamloo (حکمت و فلسفه, 2018)
The issue of "error", along with the subject of knowledge, is very important for Plato and in the context of defining knowledge as the right belief in Theaetetus, it seeks to explain the possibility of mistaken belief. He offers suggestions to explain the issue of error beliefs. He offers two proposals, one based on the concepts of knowing and not-knowing, and the other based on the concepts of being and not-being, puts two puzzles to believe in error, and both of these are two puzzles to believe in error. Then, he presents three solutions to false belief. Each of these suggestions is carefully reviewed. But all the ways will remain in vain and the efforts are fruitless. Here, Plato seeks to show that the mere reliance on detail as what true knowledge belongs to it, leads to the impossibility of explaining false belief. In this paper, different aspects of the issue of error belief are analyzed to reach Plato's views in the Theaetetus treatise.